2021
DOI: 10.1038/s41598-021-98676-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a DNA aptamer for MLL-AF9 expressing acute myeloid leukemia cells using whole cell-SELEX

Abstract: Current classes of cancer therapeutics have negative side effects stemming from off-target cytotoxicity. One way to avoid this would be to use a drug delivery system decorated with targeting moieties, such as an aptamer, if a targeted aptamer is available. In this study, aptamers were selected against acute myeloid leukemia (AML) cells expressing the MLL-AF9 oncogene through systematic evolution of ligands by exponential enrichment (SELEX). Twelve rounds of SELEX, including two counter selections against fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…We identified structural regions that account for the binding motifs of the full-length aptamers. The constant regions of aptamer sequences have often been found to participate in the functional secondary structures by interacting with the random region [ 28 , 29 , 30 , 31 ]. We also found that in the three short aptamers, the 5′ priming sequence is partly involved in the functional binding site.…”
Section: Discussionmentioning
confidence: 99%
“…We identified structural regions that account for the binding motifs of the full-length aptamers. The constant regions of aptamer sequences have often been found to participate in the functional secondary structures by interacting with the random region [ 28 , 29 , 30 , 31 ]. We also found that in the three short aptamers, the 5′ priming sequence is partly involved in the functional binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The stem-loop structure can stabilize and support the conformation of aptamers. Therefore, in case the existence of the stem-loop structure, the primer binding region should not be removed directly to avoid destroying the conformation of aptamers [ 63 , 64 ]. However, when the selected aptamers contain many stems or loops, the complex conformation may also affect the binding of aptamers and targets.…”
Section: Post-selex Optimization Of Aptamersmentioning
confidence: 99%
“…They can interact with their targets through their unique three-dimensional (3D) conformations, and specific aptamers against various targets like peptides, proteins, small inorganic ions, various complex tissues or cells, and drugs have been successfully developed . Aptamers developed from random nucleotide libraries by SELEX possess high selectivity to their molecular or cellular targets and typically bind to their targets with mid-to-low nanomolar affinity. , Therefore, aptamers are a promising analytical tool and alternative to antibodies for the detection of small molecules, proteins, viruses, whole cells, and peptides. Aptamers have greater thermal stability than antibodies, and they can be stored at ambient temperatures . In addition, aptamer affinities are not affected by labeling because labels can be incorporated at the time of aptamer synthesis in defined positions away from binding loops .…”
Section: Introductionmentioning
confidence: 99%